Preparation method of nanoscale CHNU-1 molecular sieve with controllable morphology orientation
The hydrogen-type CHNU-1 molecular sieve catalyst grown in special directions was prepared through direct synthesis method, which solved the problem of nano-level oriented molecular sieve growth control, achieved efficient catalytic life and unique product distribution, was suitable for a variety of catalytic reactions, and improved the catalyst application potential.
Patent Information
- Application Number
- CN202311812511.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-27
- Publication Date
- 2024-12-13
AI Technical Summary
The prior art is difficult to achieve controllable growth of nano-scale oriented molecular sieves, especially in the directions of b and c, which limits the diffusion efficiency of catalytic reactions and the uniqueness of product distribution, resulting in the service life and reaction process of the catalyst being affected. .
Using a direct synthesis method, by mixing silicon source, heteroatom source, crystallization auxiliary agent and deionized water in a certain proportion, adding organic template agent, and performing high-temperature roasting to prepare a special direction (x-axis or z- Axis) The hydrogen-type CHNU-1 molecular sieve catalyst grown in an orientation simplifies the process, reduces energy consumption, and realizes the controllable growth of crystals and the modulation of acidity and grain size.
Achieved efficient synthetic morphological and controllable H-CHNU-1 molecular sieve catalyst, with an ultra-long catalytic life and unique product distribution, is suitable for a variety of catalytic reactions, and avoids the ion exchange step and the introduction of alkali metal ions. , significantly improve the application potential of catalysts.
Smart Images

Figure CN119118144A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of inorganic chemical synthesis and chemical application technology, in particular to a method for preparing a special oriented CHNU-1 molecular sieve. Background Art
[0002] Oriented molecular sieve catalysts shorten the length of the pores in a specific direction and often have a large specific surface area and a distinct multi-level pore structure. While having adjustable ion exchange sites or active sites, adjustable acid amount and acid strength, they can shorten the diffusion path of guest molecules to a certain extent, reduce diffusion resistance, and improve mass transfer and diffusion efficiency. Therefore, their application in catalytic reactions often greatly prolongs the service life of the catalyst by reducing the rate of carbon deposition, and may affect the reaction process by affecting the diffusion path of guest molecules, thereby showing a unique product distribution. Oriented molecular sieves with nanoscale sizes often show better mass transfer and diffusion efficiency and catalytic life in the catalytic process. However, the crystallization process of molecular sieves is usually accompanied by the Ostwald ripening phenomenon, that is, the surface free energy of the crystal tends to be minimized. This phenomenon is more inclined to induce continuous growth of crystals, which is conducive to the acquisition of large-sized crystals, and therefore brings difficulties to the preparation of nano-oriented molecular sieve materials.
[0003] One of the common morphologies of nano-scale oriented molecular sieves is the accumulation of small nanoparticles. Although it has the advantage of nano-effect, it lacks sufficient shape-selective space, which easily causes encapsulated carbon deposition, directly leading to catalyst deactivation. Oriented nanosheets have the advantages of longer-range order of crystals, higher stability, and less prone to encapsulated carbon deposition while taking into account high mass transfer efficiency. At present, a variety of topological molecular sieves such as MFI, FER, MOR, etc. have achieved the preparation of oriented nanosheet morphology crystals, and the synthesis methods have been diversified, and the potential of oriented nanosheets in catalytic applications has also been fully explored. However, the oriented growth of various topological molecular sieves has not yet been fully controlled. For example, the oriented growth reported for the FER structure is all along the a-axis direction (10.1021 / acs.chemmater.1c01876), while the oriented morphology along the b and c directions is rarely reported. The oriented growth of MOR topological molecular sieves is mostly along the c-axis direction (10.1039 / c7ta02477k). It was not until 2020 that Lu et al. prepared nanofilament MOR crystals oriented along the b-axis direction for the first time (10.1002 / anie.202000269). Because its special oriented growth changes the diffusion efficiency of guest molecules in the catalytic reaction, the MOR nanofilaments oriented along the b-axis show unique high selectivity for ethylene in the methanol conversion to hydrocarbons (MTH) reaction, which is completely different from the product distribution of the MTH reaction catalyzed by conventional morphology and conventional oriented MOR molecular sieves. Therefore, the potential of molecular sieve materials with unconventional orientation in catalytic applications is unlimited, and breaking through the preparation bottleneck and realizing the synthesis of unconventional oriented materials is the first problem that must be overcome to realize the catalytic performance research of special oriented materials. Summary of the invention
[0004] Based on the deficiencies and development space of the prior art, the present invention discloses a direct synthesis method of a CHNU-1 molecular sieve with controllable nanoscale morphology and orientation. After a silicon source, a heteroatom source free of alkali metals and alkaline earth metals, a crystallization auxiliary agent and deionized water are mixed in a certain proportion, an organic template agent of a certain type and input amount is added, and the sample after crystallization for a period of time is directly calcined at high temperature to obtain a hydrogen-type CHNU-1 molecular sieve catalyst oriented and grown in a special direction. The preparation process is simple and the synthesis efficiency is high. The obtained sample can be used directly as a catalyst, omitting the ion exchange and other links, greatly reducing energy consumption and shortening the process; the controllable growth of the crystal is achieved, and a CHNU-1 molecular sieve catalyst with a special orientation and controllable mode (along the x-axis or z-axis direction) is prepared by a one-step synthesis method, and its acidity and grain size are easy to adjust, and it shows an ultra-long catalytic life and a unique product distribution in reactions such as methanol conversion to hydrocarbons, and has great application potential. The method of the present invention provides a cheap and easy-to-operate strategy for synthesizing heteroatom special orientation molecular sieves.
[0005] The present invention adopts the following technical solution:
[0006] A preparation method of a nano-scale CHNU-1 molecular sieve with controllable morphology and orientation, characterized in that: a compound containing at least one element of heteroatoms B, Ga, Fe, P, Sn and Ti is used as a heteroatom source, and at least one of fumed silica, silica gel, amorphous silicon oxide, tetraethyl orthosilicate, silica sol, silicon-based molecular sieve and silicate is used as a silicon source; the heteroatom source, silicon source and deionized water are uniformly mixed; a template agent and a crystallization auxiliary agent are added, crystallized in a reactor, and then the sample after crystallization is calcined in an air atmosphere to obtain the target product, a nano-scale CHNU-1 molecular sieve. The obtained solid powder is an H-CHNU-1 molecular sieve with heteroatoms embedded in the skeleton.
[0007] Furthermore, the molar ratio of the reactants is Si:M:D:A:H2O=1:1~0:2.5~0.01:1~0:1~120, wherein Si represents the molar amount of Si contained in the silicon source, M represents the molar amount of the heteroatom oxide form, D represents the molar amount of the template, and A represents the molar amount of the crystallization auxiliary agent.
[0008] Furthermore, in the heteroatom source, the raw material containing B is boric acid or its oxide, the raw material containing Ga or Fe is the nitrate or chloride corresponding to the Ga or Fe element, the raw material containing P is ammonium hydrogen phosphate or diammonium dihydrogen phosphate, the raw material containing Sn is SnCl4·5H2O or other tin-containing salts, and the raw material containing Ti is tetrabutyl titanate, tetraethyl titanate, TiCl3·6H2O or other titanium-containing salts.
[0009] Furthermore, the template agent is at least one of TPAOH (tetrapropylammonium hydroxide), ethylenediamine, ethylamine, triethylamine, n-butylamine, TPABr (tetrapropylammonium bromide), imidazole salts, pyrrolidine salts, piperidine salts, HMI (hexamethyleneimine), CTAB (dodecyltrimethylammonium bromide) and other organic substances.
[0010] Furthermore, the crystallization auxiliary agent is at least one of NH3·H2O, NH4Cl, ammonium fluoride and hydrogen fluoride.
[0011] Furthermore, the crystallization temperature is 100-200°C, and the crystallization time is 2-25 days. The crystallization time is preferably 4-18 days; and the crystallization temperature is preferably 120-180°C.
[0012] Furthermore, the calcination temperature is 550° C. and the calcination time is 6 hours.
[0013] In the above scheme, the molecular sieve topology that can be used as a silicon source includes at least one of MFI, *BEA, FER and FAU.
[0014] The heteroatoms involved in the method of the present invention are not limited to those described herein, and the method of the present invention is not excluded from being applied to the direct synthesis of H-CHNU-1 molecular sieves containing other heteroatoms, wherein the other heteroatoms include V, In, Ge, Co, Ni, Bi, Zn, Cr, etc.
[0015] The beneficial effects of the present invention are embodied in:
[0016] 1. The method of the present invention can directly and efficiently synthesize H-CHNU-1 molecular sieve catalyst with controllable morphology and orientation, with a yield close to 100%, and no additional seed crystals are required during the synthesis process, thus avoiding other costs during the synthesis process.
[0017] 2. The molecular sieve material obtained by the present invention is not of the common molecular sieve size, but has a nanoscale morphology and good crystallinity. The obtained material does not introduce alkali metal and alkaline earth metal ions, and does not require an exchange step. At the same time, the nanoscale molecular sieve material obtained by the present invention is different from the conventional nanoparticles and oriented nanosheet morphology. The orientation of the morphology is unconventional, and the growth in this orientation direction has never been reported.
[0018] 3. The present invention is a method that can be used without introducing Na + The invention discloses a method for directly preparing hydrogen-type molecular sieves by controlled growth under working conditions such as alkali metal ions, which has a simple process and high synthesis efficiency. The invention realizes the controllable growth of crystals, and adopts a one-step synthesis method to prepare a CHNU-1 molecular sieve catalyst oriented in a special direction that has never been reported, and its acidity and grain size are easy to adjust. It exhibits an ultra-long catalytic life and unique product distribution in the methanol conversion reaction to produce hydrocarbons, and has great application potential.
[0019] 4. The specially oriented CHNU-1 molecular sieve prepared by the present invention can be used in multiple fields, including: as a catalyst for catalyzing thermal catalytic reactions and photoelectrocatalytic reactions such as methanol to hydrocarbons (MTP, MTO, MTA, MTG, MTH), catalytic cracking, catalytic oxidation, alkylation, epoxidation, BV oxidation, ammoximation, etc.; it can also be used as an adsorbent for organic matter, gas, radioactive pollution sources and heavy metal ions; it can also be used as a carrier for other catalysts. The molecular sieve synthesized by the present invention is an H-type molecular sieve, which does not require ion exchange, avoids the wastewater generated by the process and the additional energy consumption, can be directly applied to the acid catalytic system, and the acidity of the molecular sieve is easy to adjust, and the applicable catalytic reaction range is wide. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a scanning electron microscope image of the molecular sieve synthesized in Example 1.
[0021] Figure 2 This is the nitrogen adsorption-desorption isotherm of the molecular sieve synthesized in Example 1.
[0022] Figure 3 This is a transmission electron microscope image of the molecular sieve synthesized in Example 1, and the inset is its diffraction spot.
[0023] Figure 4 This is a scanning electron microscope image of the molecular sieve in Example 2.
[0024] Figure 5 This is a transmission electron microscopy image of the molecular sieve synthesized in Example 2, and the inset is its diffraction spots.
[0025] Figure 6 This is a scanning electron microscope image of the molecular sieve synthesized in Example 5.
[0026] Figure 7 This is the UV-visible absorption spectrum of the molecular sieve synthesized in Example 5.
[0027] Figure 8 This is a scanning electron microscope image of the molecular sieve synthesized in Example 6.
[0028] Fig. 9 This is the UV-visible absorption spectrum of the molecular sieve synthesized in Example 6. Specific embodiments
[0029] The present invention is further described below in conjunction with the embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1
[0031] After tetraethyl orthosilicate, boric acid, ammonium fluoride and deionized water were stirred until uniformly mixed, they were transferred to a high-pressure reactor with a 100 mL polytetrafluoroethylene liner, and a certain mass of 1-butyl-3-methylimidazolium hydroxide was added as a template agent; the initial molar ratio of the reactants was Si:B:D:A:H2O=1:1 / 120:0.2:0.1:6. Crystallization was carried out at 140°C for 12 days, and the solid product was calcined at 550°C for 6 hours to remove the template agent, and a nanoscale special orientation morphology CHNU-1 molecular sieve was obtained, and the solid product yield was calculated to be 98.6%.
[0032] Wherein, 1-butyl-3-methylimidazolium hydroxide is obtained by exchanging 1-butyl-3-methylimidazolium chloride with a hydroxyl exchange resin.
[0033] See also Figure 1 The CHNU-1 molecular sieve prepared in Example 1 was shown by scanning electron microscopy to be bamboo-leaf-shaped primary crystal clusters, and the sample had clear edges and good crystallinity.
[0034] See also Figure 2 The nitrogen adsorption-desorption isotherm of the CHNU-1 molecular sieve prepared in Example 1 shows that the material has a rich multi-level pore structure and a large specific surface area.
[0035] See also Figure 3 The CHNU-1 molecular sieve prepared in Example 1 was shown by transmission electron microscopy to have inhibited growth along the x-axis direction, and the scale along the x-axis direction was 15 nanometers.
[0036] Example 2
[0037] Fuming silica gel, gallium nitrate, 1,3-bis(2,6-diisopropylphenyl)imidazolium hydroxide and deionized water were mixed and stirred thoroughly, and the mixture was transferred to a high-pressure reactor with a 100 mL polytetrafluoroethylene liner, and a certain mass of hydrogen fluoride was added as a crystallization auxiliary agent. The molar ratio of the obtained mixture was Si:Ga:D:A:H2O=1:1 / 20:0.45:0.5:5 (D is 1,3-bis(2,6-diisopropylphenyl)imidazolium hydroxide). Crystallization was carried out at 170°C for 6 days, and the solid product was calcined at 550°C for 6 hours to remove the template agent, thereby obtaining a CHNU-1 molecular sieve with a special orientation morphology, and the solid product yield was calculated to be 99.0%.
[0038] Wherein, 1,3-bis(2,6-diisopropylphenyl)imidazolium hydroxide is obtained by exchanging 1,3-bis(2,6-diisopropylphenyl)imidazolium chloride with a hydroxy-type exchange resin.
[0039] See also Figure 4 The CHNU-1 molecular sieve prepared in Example 2 was shown by scanning electron microscopy to be bamboo-leaf-shaped primary crystals randomly stacked, with clear edges and good crystallinity.
[0040] See also Figure 5 The CHNU-1 molecular sieve prepared in Example 2 was shown by transmission electron microscopy to have inhibited growth along the x-axis direction, and the scale along the x-axis direction was 18 nanometers.
[0041] Example 3
[0042] White carbon black, boric acid, dodecylpyridinium hydroxide and deionized water were stirred evenly, and the mixture was placed in a high-pressure reactor equipped with a 100mL polytetrafluoroethylene liner, and ammonium fluoride was added as a crystallization auxiliary agent. The initial molar ratio of the reactants was Si:B:D:A:H2O=1:1 / 15:0.3:0.5:10 (D is dodecylpyridinium hydroxide). Crystallization was carried out at 170°C for 4 days, and the solid product was calcined at 550°C for 6h to remove the template agent, and a specially oriented hydrogen-type CHNU-1 molecular sieve was obtained, and the solid product yield was calculated to be 94.5%.
[0043] Wherein, dodecylpyridinium hydroxide is obtained by exchanging dodecylpyridinium chloride with a hydroxy-type exchange resin.
[0044] Example 4
[0045] The synthesis operation in Example 3 was repeated, but the crystallization time was extended to 12 days, and the obtained solid product was calcined at 550° C. for 6 hours to remove the template, and another CHNU-1 molecular sieve with an oriented morphology of nano-scale grain size was obtained, which had an x-axis orientation and a y-axis dimension in the nanometer range. The yield of the solid product prepared in this example was 98.9%.
[0046] Example 5
[0047] The operation is carried out in reference to Example 3, except that the boron source involved in the crystallization is replaced by a titanium source (tetrabutyl titanate), the initial molar ratio of the reactants is Si:Ti:D:A:H2O=1:1 / 60:0.3:0.5:10, the crystallization time is 6 days, and the obtained product is calcined at 550°C for 6h to remove the template to obtain a titanium-containing CHNU-1 molecular sieve having the same special orientation morphology, and the solid product yield is calculated to be 98.0%.
[0048] See also Figure 6 The CHNU-1 molecular sieve prepared in Example 5 was shown by scanning electron microscopy to be cross-stacked nanosheets of about 70 nanometers, and the sample had clear edges and good crystallinity.
[0049] See also Figure 7 The UV-visible absorption spectrum of the CHNU-1 molecular sieve prepared in Example 5 shows that the titanium species in the sample are almost all framework tetracoordinate titanium species.
[0050] Example 6
[0051] The operation was performed with reference to Example 3, except that the boron source involved in the crystallization was replaced with a tin source (tin tetrachloride pentahydrate), the initial molar ratio of the reactants was Si:Sn:D:A:H2O=1:1 / 80:0.3:0.5:10, the crystallization time was 6 days, and the obtained product was calcined at 550°C for 6h to remove the template to obtain a tin-containing CHNU-1 molecular sieve with a special oriented morphology, and the solid product yield was calculated to be 95.0%.
[0052] See also Figure 8 The CHNU-1 molecular sieve prepared in Example 6 was shown by scanning electron microscopy to be cross-stacked 60-90 nanometer plate-like crystals, and the sample had clear edges and good crystallinity.
[0053] See also Fig. 9 The UV-visible absorption spectrum of the CHNU-1 molecular sieve prepared in Example 6 shows that the tin species in the sample are almost all framework tetracoordinated tin species.
[0054] Example 7
[0055] After tetraethyl orthosilicate, boric acid, hydrogen fluoride and water are stirred until uniformly mixed, they are placed in a high-pressure reactor with a 100 mL polytetrafluoroethylene liner, and a certain mass of 1-ethyl-3-methylimidazole hydroxide and CTAB are added; the initial molar ratio of the reactants is Si:B:D1:D2:A:H2O=1:1 / 80:0.2:0.05:0.5:25 (D1 is 1-ethyl-3-methylimidazole hydroxide, D2 is CTAB). Crystallization is carried out at 120°C for 16 days, and the solid product is calcined at 550°C for 6 hours to remove the template agent to obtain a nanoscale special orientation morphology CHNU-1 molecular sieve, and the solid product yield is calculated to be 96.2%. The relative crystallinity of the obtained sample is good, and the boron source in the crystallization system can be replaced by other metals, and the crystallization can be completed by extending the time.
[0056] Wherein, 1-ethyl-3-methylimidazole hydroxide is obtained by exchanging 1-ethyl-3-methylimidazole chloride with a hydrogen-oxygen exchange resin.
[0057] Example 8
[0058] After stirring silica sol, titanium sulfate, ammonium fluoride and water until they are evenly mixed, they are placed in a high-pressure reactor with a 100 mL polytetrafluoroethylene liner, and a certain mass of 2-isopropylimidazole and TPAOH are added; the initial molar ratio of the reactants is Si:Ti:D1:D2:A:H2O=1:1 / 100:0.35:0.1:0.5:6 (D1 is 2-isopropylimidazole, D2 is TPAOH). Crystallization is carried out at 120°C for 16 days, and the solid product is calcined at 550°C for 6 hours to remove the template agent to obtain a nanoscale special orientation morphology CHNU-1 molecular sieve. The relative crystallinity of the obtained sample is good, and the calculated solid product yield is 95.5%. The titanium source can be replaced with other metals in the crystallization system, and the crystallization can also be completed by extending the time.
[0059] Example 9
[0060] After stirring silica sol, tin tetrachloride pentahydrate, ammonium fluoride and water until uniformly mixed, they were placed in a 100 mL polytetrafluoroethylene lined autoclave, and a certain mass of 2-isopropylimidazole and TPAOH were added; the initial molar ratio of the reactants was Si:Sn:D1:D2:A:H2O=1:1 / 90:0.25:0.1:0.5:6 (D1 was 2-isopropylimidazole, D2 was TPAOH). Crystallization was carried out at 150°C for 16 days, and the solid product was calcined at 550°C for 6 hours to remove the template, and a nanoscale special oriented morphology tin-containing CHNU-1 molecular sieve was obtained, and the solid product yield was calculated to be 93.4%.
[0061] Example 10
[0062] After stirring silica sol, titanium sulfate, ammonium fluoride and water until they are uniformly mixed, they are placed in a 100 mL polytetrafluoroethylene-lined autoclave, and a certain mass of 2-isopropylimidazole and TPAOH are added; the initial molar ratio of the reactants is Si:Ti:D1:D2:A:H2O=1:1 / 60:0.25:0.1:0.5:6 (D1 is 2-isopropylimidazole, D2 is TPAOH). Crystallization is carried out at 150°C for 16 days, and the solid product is calcined at 550°C for 6 hours to remove the template, thereby obtaining a nano-scale titanium-containing CHNU-1 molecular sieve with a special orientation morphology.
[0063] Embodiment 11
[0064] The sample obtained in Example 1 was used in a MTP (methanol to propylene) fixed bed reaction under the following reaction conditions: 0.1 g of catalyst was placed in a reactor and nitrogen was used (flow rate 30 mL min -1 ) was activated at 500°C for 1 hour and reacted at 450°C with a methanol space velocity of 1.67 h -1 The reaction results were analyzed by gas chromatography (Kechuang GC-9800). Compared with the micron-sized bulk catalyst (Bulk, 10.1016 / j.apcatb.2017.04.001), the propylene selectivity of CHNU-1 can reach up to 59%, and it has an extremely long life of 169 hours (the life is defined as the time when the conversion rate is greater than or equal to 99%, the same below).
[0065] Table 1 Selectivity of each product component in MTP reaction (methanol conversion ≥ 99%)
[0066]
[0067]
[0068] Example 12
[0069] The sample obtained in Example 2 was used for MTP reaction, activation and activity test operations were the same as in Example 11, and the results showed ultra-high propylene selectivity (greater than 60%) and reaction life (145 hours), and the propylene-ethylene ratio (P / E) was extremely high, with a value greater than 15.
[0070] Table 2. Propylene selectivity and P / E ratio of catalysts with the same topological structure and different oriented morphologies in MTP reaction
[0071]
[0072] Source literature of each comparison sample in Table 2:
[0073] [1]Li,J.;Liu,S.;Zhang,H.;Lü,E.;Ren,P.;Ren,J.Synthesis andCharacterization of an Unusual Snowflake-Shaped ZSM-5Zeolite with HighCatalytic Performance in the Methanol to Olefin Reaction.ChineseJournalofCatalysis 2016,37(2),308–315.https: / / doi.org / 10.1016 / S1872-2067(15)60979-2.
[0074] [2]Rostamizadeh,M.;Yaripour,F.;Hazrati,H.High Efficient MesoporousHZSM-5Nanocatalyst Development through Desilication with MixedAlkalineSolution for Methanol to Olefin Reaction.JPorousMater 2018,25(5),1287–1299.https: / / doi.org / 10.1007 / s10934-017-0539-2.
[0075] [3]Feng,R.;Yan,X.;Hu,X.;Wu,J.;Yan,Z.Direct Synthesis ofB-AxisOriented H-Form ZSM-5Zeolites with an Enhanced Performance in the Methanol toPropylene Reaction.Microporous Mesoporous Mater.2020,302,110246.https: / / doi.org / 10.1016 / j.micromeso.2020.110246.
[0076] [4]Zhou,J.;Teng,J.;Ren,L.;Wang,Y.;Liu,Z.;Liu,W.;Yang,W.;Xie,Z.Full-Crystalline Hierarchical Monolithic ZSM-5Zeolites as Superiorly Active andLong-Lived Practical Catalysts in Methanol-to-HydrocarbonsReaction.J.Catal.2016,340,166–176.https: / / doi.org / 10.1016 / j.jcat.2016.05.009.
[0077] [5]Zhang,Y.;Luo,P.;Xu,H.;Han,L.;Wu,P.;Sun,H.;Che,S.Hierarchical MFIZeolites with a Single-Crystalline Sponge-Like Mesostructure.Chem.Eur.J.2018,24(72),19300–19308.https: / / doi.org / 10.1002 / chem.201804193.
[0078] [6]Dai,W.;Kouvatas,C.;Tai,W.;Wu,G.;Guan,N.;Li,L.;Valtchev,V.PlatelikeMFI Crystals with Controlled Crystal Faces AspectRatio.J.Am.Chem.Soc.2021,143(4),1993–2004.https: / / doi.org / 10.1021 / jacs.0c11784.
[0079] [7]Ma, Y.; Tang, X.; Hu, J.; Ma, Y.; Chen, W.; Liu, Z.; Han, S.; Xu, C.; Wu, Q.; Zheng, A.; Zhu, L.; Meng, X.; Xiao, F.-S. Nanosheets.J.Am.Chem.Soc.2022,144(14),6270–6277.https: / / doi.org / 10.1021 / jacs.1c12338.
[0080] Embodiment 13
[0081] The sample obtained in Example 3 was used in the alkylation reaction of benzene. The alkylation reaction performance test of benzene and ethanol was carried out on a fixed bed apparatus. 0.1 g of catalyst (60-80 mesh) was placed in the middle of the reactor and heated at 623 K, 30 mL min -1 The mixture was activated in nitrogen gas at a flow rate of 2 h for 2 h, and then cooled to 473 K for reaction. The reactants, benzene and ethanol, were prepared into a solution with a molar ratio of 3 and injected into the reactor. The ethanol hourly velocity (WHSV) was 2 h -1 The products were analyzed by gas chromatography (Kechuang GC-9800). Compared with bulk (10.1002 / chem.201804193) morphology catalyst, CHNU-1 showed good conversion (88%) and ethylbenzene selectivity (nearly 100%).
[0082] Embodiment 14
[0083] The sample obtained in Example 5 was used for Beckmann rearrangement reaction: The Beckmann rearrangement reaction of cyclohexanone oxime was also tested on a fixed bed apparatus. 0.1 g of the sieved catalyst (60-80 mesh) was placed in the reaction apparatus and heated at 20 mL min -1 The mixture was activated at 723 K for 1 hour under a nitrogen flow rate of 1.5 % and then cooled to 623 K for reaction. A solution of cyclohexanone oxime and methanol in a mass ratio of 1:9 was pumped into the reaction device at a feed rate of 15 g h -1 The selectivity of the rearrangement product was as high as 99.9% as determined by gas chromatography.
[0084] The above embodiments are only for further explanation of the present invention. The protection content of the present invention is not limited to the above embodiments. Without departing from the spirit and scope of the inventive concept, changes and advantages that can be thought of by those skilled in the art are all included in the present invention and are protected by the attached claims.
Claims
1. A method for preparing a nano-scale CHNU-1 molecular sieve with controllable morphology and orientation, characterized in that: A compound containing at least one element of heteroatom B, Ga, Fe, P, Sn and Ti is used as a heteroatom source, and at least one of fumed silica, silica gel, amorphous silicon oxide, tetraethyl orthosilicate, silica sol, silicon-based molecular sieve and silicate is used as a silicon source; the heteroatom source, silicon source and deionized water are uniformly mixed; a template agent and a crystallization auxiliary agent are added, crystallization is carried out in a reactor, and then the sample after crystallization is calcined in an air atmosphere to obtain a nano-scale CHNU-1 molecular sieve.
2. The method for preparing nano-scale CHNU-1 molecular sieve with controllable morphology and orientation according to claim 1, characterized in that: The molar ratio of reactants is Si:M:D:A:H2O=1:1~0:2.5~0.01:1~0:1~120, wherein Si represents the molar amount of Si contained in the silicon source, M represents the molar amount of heteroatom oxide form, D represents the molar amount of template agent, and A represents the molar amount of crystallization auxiliary agent.
3. The method for preparing nano-scale CHNU-1 molecular sieve with controllable morphology and orientation according to claim 1, characterized in that: Among the heteroatom sources, the raw material containing B is boric acid or its oxide, the raw material containing Ga or Fe is the nitrate or chloride corresponding to the Ga or Fe element, the raw material containing P is ammonium hydrogen phosphate or diammonium dihydrogen phosphate, the raw material containing Sn is SnCl4·5H2O or other tin-containing salts, and the raw material containing Ti is tetrabutyl titanate, tetraethyl titanate, TiCl3·6H2O or other titanium-containing salts.
4. The method for preparing nano-scale CHNU-1 molecular sieve with controllable morphology and orientation according to claim 1, characterized in that: The template agent is at least one of tetrapropylammonium hydroxide, ethylenediamine, ethylamine, triethylamine, n-butylamine, tetrapropylammonium bromide, imidazole salts, pyrrolidine salts, piperidine salts, hexamethyleneimine, hexadecyltrimethylammonium bromide and other ammonium salts.
5. The method for preparing nano-scale CHNU-1 molecular sieve with controllable morphology and orientation according to claim 1, characterized in that: The crystallization auxiliary agent is at least one of NH3·H2O, NH4Cl, ammonium fluoride and hydrogen fluoride.
6. The method for preparing nano-scale CHNU-1 molecular sieve with controllable morphology and orientation according to claim 1, characterized in that: The crystallization temperature is 100-200° C. and the crystallization time is 2-25 days.
7. The method for preparing nano-scale CHNU-1 molecular sieve with controllable morphology and orientation according to claim 1, characterized in that: The calcination temperature is 550° C. and the calcination time is 6 hours.
8. A method for preparing nano-scale CHNU-1 molecular sieve with controllable morphology and orientation obtained by the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Double heteroatoms iron-titanium aluminum-free nano zeolite molecular sieve rapid synthesis method
CN101007638A
Method for directly preparing M-HZSM-5 molecular sieve
CN111495421A
Preparation method of hydrogen type silica-alumina ZSM-48 molecular sieve
CN113548676A
Preparation and modification method of sodium-free synthesized hierarchical porous ZSM-5 molecular sieve
CN114655966A
